PENGGUNAAN MATERNAL EMERGENCY SCREENING (MES) SEBAGAI UPAYA DETEKSI DINI PADA KEGAWATDARURATAN KEHAMILAN - Azlina, Fitri Ayatul (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2018)
Maternal mortality rate (MMR) in Indonesia is still high. Various programs that have been doneby the government try to decrease the AKI both promotively and preventively during pregnancyand before childbirth. Nurses play an important role in efforts to minimize and reduce MMRthrough various methods one of them with the utilization of information technology. Not onlynurses, pregnant women should play an active role in finding symptoms and risk factors duringpregnancy. Maternal Emergency Screening (MES) is an information technology design usingexpert systems that can facilitate pregnant women in identifying early risk factors in emergencyemergency and able to make decisions like an expert. The use of Maternal Emergency Screening(MES) provides an opportunity as an early screening system in finding risks of emergencypregnancy and helps nurses to take appropriate care measures in order to reduce MMR.